On the Conforming Combination of the Electric and Magnetic Field Integral Equations - Yilmaz, Ahmet F.; Ulku, H. Arda (IEEE, 2018)
A scheme to conformingly combine the electric and field integral equations (EFIE and MFIE) is presented. Particularly the range space of the method of moments (MoM) matrix system for the mixed discretized MFIE is projected to the range space of the classically discretized EFIE and then combined with EFIE. As a result, an accurate, interior resonance free, and ideally combination factor independent matrix system for the combined field integral equation (CFIE) is obtained. Numerical examples that demonstrate the accuracy and combination factor dependence are presented.
International Applied Computational Electromagnetics Society Symposium (ACES) -- MAR 25-29, 2018 -- Denver, CO
Keywords: combined field integral equation (CFIE); interior resonance problem; mixed discretization